Adenosine diphosphate-decorated chitosan nanoparticles shorten blood clotting times, influencing the structures and varying the mechanical properties of the clots - Chung TW (Dove Medical Press, 2014)
Tze-Wen Chung,1,3 Pei-Yi Lin,2 Shoei-Shen Wang,2 Yen-Fung Chen31Department of Biomedical Engineering, National Yang-Ming University, 2Department of Surgery, National Taiwan University Hospital, Taipei, Taiwan, Republic of China; 3Department of Chemical and Materials Engineering, National Yunlin University of Science and Technology, Yunlin, Taiwan, Republic of ChinaAbstract: Chitosan nanoparticles (NPs) decorated with adenosine diphosphate (ADP) (ANPs) or fibrinogen (FNPs) were used to fabricate hemostatic NPs that can shorten blood clotting time and prevent severe local hemorrhage. The structure and mechanical properties of the blood clot induced with ANP (clot/ANP) or FNP (clot/FNP) were also investigated. The NPs, ANPs, and FNPs, which had particle sizes of 245.1±14.0, 251.0±9.8, and 326.5±14.5 nm and zeta potentials of 24.1±0.5, 20.6±1.9, and 15.3±1.5 mV (n=4), respectively, were fabricated by ionic gelation and then decorated with ADP and fibrinogen. The zeta potentials and Fourier transform infrared (FTIR) spectroscopy of the NPs confirmed that their surfaces were successfully coated with ADP and fibrinogen. The scanning electron microscope (SEM) micrographs of the structure of the clot induced with "undecorated" chitosan NPs (clot/NP), clot/ANP, and clot/FNP (at 0.05 wt%) were different, after citrated bloods had been recalcified by a calcium chloride solution containing NPs, ANPs, or FNPs. This indicated that many NPs adhered on the membrane surfaces of red blood cells, that ANPs induced many platelet aggregates, and that FNPs were incorporated into the fibrin network in the clots. Measurements of the blood clotting times (Tc) of blood clot/NPs, clot/ANPs, and clot/FNPs, based on 90% of ultimate frequency shifts measured on a quartz crystal microbalance (QCM), were significantly (P<0.05) (n=4) shorter than that of a clot induced by a phosphate-buffered solution (PBS) (clot/PBS) (63.6%±3.1%, 48.3%±6.2%, and 63.2%±4.7%, respectively). The ∆F2 values in the spectra of frequency shifts associated with the propagation of fibrin networks in the clot/ANPs and clot/FNPs were significantly lower than those of clot/PBS. Interestingly, texture profile analysis of the compressional properties showed significantly lower hardness and compressibility in clot/NPs and clot/ANPs (P<0.05 or better) (n=4) compared with clot/PBS and clot/FNPs. Accordingly, among the hemostatic NPs, ANP substantially reduced blood clotting times, ∆F2 values, and compression flow properties of the clot. Hence, ANPs have potential applications for preventing severe local hemorrhage.Keywords: hemostatic NPs, ADP, fibrinogen, compressional properties